Kehidupan Sosial dan Spiritual Formation Mahasiswa Indekos di Lingkungan Kampus - Kartini Leidy Prily Rorong; Johan N. Gara; Wolter Weol (Peneliti.net, 2021)
The purpose of this study was to obtain the results of the analysis and description of the student's social life influenced by the campus environment, family environment, and boarding house environment which influence each other so that the spiritual formation of students is needed to erode the emerging influences. Also raised the problems of boarding students in the environment around the campus. Raising the context of social life and spiritual formation with the problems of boarding house students in the campus environment, and the efforts that need to be made to overcome polemics in the field. The research uses qualitative research methods as an effort to present the social world, and its perspective in the world, in terms of concepts, behaviors, perceptions, and issues about the human being studied. This is what becomes a reference for researchers in finding and collecting data in the field, with boarding house research locations around the IAKN Manado campus